A sodium ion battery hard carbon negative electrode slurry and its use in vehicles
By using specific dispersants and auxiliary materials in the hard carbon anode slurry of sodium ion batteries, the problem of too small viscosity and unsatisfactory dispersion effect of the hard carbon anode slurry is solved, and higher conductivity and electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411428568.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The viscosity of the hard carbon negative electrode slurry of sodium ion battery is too small and the dispersion effect is not ideal, which leads to the impact of electrochemical performance.
Excipients including conductive agents, thickeners, binders, binders and dispersants are used, especially glyceryl acrylate and cocoyl diethanolamine as dispersants, to improve the dispersion performance of the material in the slurry, and to adjust the viscosity of the slurry through specific stirring and vacuum treatment steps.
The dispersion performance and conductivity of the hard carbon negative electrode slurry are improved, the interface impedance is reduced, and the electrochemical performance and cycling capacity retention are improved.
Smart Images

Figure CN118970040B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery hard carbon negative electrode slurry and application thereof in vehicles. Background Art
[0002] The mixing of lithium battery cell slurry has an impact of more than 30% on the quality of the product in the entire production process of lithium-ion batteries, and is the most important link in the entire production process. The negative electrode slurry is composed of adhesives, graphite and conductive agents. The preparation of the slurry includes a series of process processes such as mixing, dissolving and dispersing between liquid and liquid, liquid and solid materials. In this process, accompanied by changes in temperature, viscosity, environment, etc., the dispersion and uniformity of the granular active material directly affect the movement of lithium ions between the two poles of the battery. Therefore, the mixing and dispersion of the slurry of each pole material is crucial in the production of lithium-ion batteries.
[0003] Sodium ion batteries and lithium ion batteries have similar working principles, and the negative electrodes are highly similar. Patent CN107293706A stirs the active material, conductive agent and thickener in a blender at a low speed to form a mixed powder, adds solvent in batches to stir and disperse to form a mixed solution, and finally adds a binder to stir and disperse to obtain a lithium ion battery negative electrode slurry; the negative electrode slurry preparation method is to first disperse the conductive agent with a thickener solution at a high speed in a double planetary manner, then add the negative electrode active material, stir at a high speed for a certain period of time, adjust the viscosity, and then add the binder to stir for a short time to obtain the final negative electrode slurry. The lower the viscosity of this method at high-speed dispersion, the less ideal the dispersion state. The solid content of the graphite negative electrode slurry prepared by this method is often between 40% and 50%. Hard carbon is an amorphous carbon material, and its microstructure has disordered graphite-like layers, abundant edge and surface defects, and a unique nanopore structure. Due to the large difference in the structure of hard carbon and graphite, it is necessary to add a binder and a conductive agent to improve its cycle performance. When sodium carboxymethyl cellulose solvent is used as a thickener, if such a more traditional method is used to prepare hard carbon slurry, the viscosity during high-speed dispersion will be too small, the dispersion effect will be unsatisfactory, and the purpose of uniform dispersion will not be achieved. The viscosity after high-speed dispersion is less than the coating range requirement, and the subsequent coating process cannot be carried out. Therefore, the prior art urgently needs a method for preparing hard carbon negative electrode slurry for sodium ion batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a sodium ion battery hard carbon negative electrode slurry and its use in a vehicle, so as to solve the problems that the viscosity of the sodium ion battery hard carbon negative electrode slurry is too low, the dispersion effect is not ideal, and it cannot be evenly dispersed, thereby affecting its electrochemical performance.
[0005] In order to solve the above technical problems, the present invention specifically provides the following technical solutions:
[0006] A sodium ion battery hard carbon negative electrode slurry, comprising: an active substance, auxiliary materials and a solvent; the auxiliary materials include a conductive agent, a thickener, a binder, an adhesive and a dispersant; the dispersant includes at least one of polyvinyl pyrrolidone, polyethylene glycol, tung oil acid glyceryl acrylate and cocoyl diethanolamine. The use of tung oil acid glyceryl acrylate and cocoyl diethanolamine can effectively improve the dispersion performance of the material in the slurry, so that the solid particles are evenly distributed in the slurry. It can also protect the structural stability of the electrode during the coating process, prevent the electrode from sticking, perforating, and softening, improve the conductivity of the electrode, reduce the interface impedance, and improve the electrochemical performance.
[0007] Preferably, the active material is hard carbon; the conductive agent is at least one of Super P, Ketjen black, and CNT; the thickener is sodium carboxymethyl cellulose; the binder is PAA; the adhesive is SBR; and the solvent is water.
[0008] The present invention discloses a method for preparing a hard carbon negative electrode slurry for a sodium ion battery, comprising:
[0009] The thickener is first mixed with water and stirred, and then a binder and a dispersant are added in sequence and stirred to obtain a thickener solution; the active material, the conductive agent, the thickener and the water are stirred and mixed, and then dispersed to obtain a dispersed powder; then the obtained thickener solution and the dispersed powder are stirred and dispersed to obtain a high-viscosity stirred slurry, and the slurry viscosity is adjusted, and then a binder is added and stirred and dispersed, and vacuum treatment is performed to obtain a sodium ion battery hard carbon negative electrode slurry.
[0010] Preferably, the thickener is sodium carboxymethyl cellulose; the thickener and deionized water in the thickener solution are mixed in a mass ratio of 1:48-150, and the mass ratio of the amount of the thickener used in the thickener solution to the amount of the active substance used is 1:400-500.
[0011] Preferably, the binder is PAA, and the mass ratio of the amount of the binder used to the amount of the active substance used is 1:35-100; the dispersant includes at least one of polyvinyl pyrrolidone, polyethylene glycol, tung oil glyceryl acrylate and cocoyl diethanolamine, and the mass ratio of the amount of the dispersant used to the amount of the active substance used is 1:50-250.
[0012] Preferably, the active material is hard carbon, the conductive agent is at least one of Super P, Ketjen black, and CNT, the mass ratio of the conductive agent to the active material is 1:46-100, the mass ratio of the thickener to the active material in the dispersed powder is 1:180-220, the active material is divided into 2-4 equal parts and added in batches for mixing, and the solid content of the dispersed powder is 92-95%.
[0013] Preferably, the viscosity of the slurry is adjusted to 3000-5000 mPa•s; the binder is SBR, and the mass ratio of the amount of SBR used to the amount of the active substance used is 1:23-100.
[0014] Preferably, during the preparation of the thickener solution, the thickener and water are mixed and stirred for 180-240 min, the binder is added and stirred for 25-40 min, and the dispersant is added and stirred for 25-40 min.
[0015] Preferably, during the preparation of the dispersed powder, the stirring and mixing time is 8-15 min, the dispersion line speed is 10-15 m / s, and the dispersion time is 40-60 min.
[0016] Preferably, the dispersion line speed of the thickener solution and the dispersed powder is 17-20 m / s, and the stirring and dispersing time is 90-120 min; after SBR is added, the dispersion line speed of the stirring and dispersing is 4-10 m / s, the stirring and dispersing temperature is 25-35°C, and the stirring and dispersing time is 20-40 min.
[0017] The present invention discloses a method for preparing a hard carbon negative electrode slurry for a sodium ion battery, and the specific steps are as follows:
[0018] The thickener is first mixed with water and stirred for 180-240 minutes, then the binder is added and stirred for 25-40 minutes, and then the dispersant is added and stirred for 25-40 minutes to obtain a thickener solution. The active material, conductive agent, thickener and water are mixed and stirred for 8-15 minutes, and then dispersed at a dispersion line speed of 10-15m / s for 40-60 minutes to obtain a dispersed powder. The obtained thickener and dispersed powder are dispersed at a dispersion line speed of 17-20m / s for 90-120 minutes to obtain a high-viscosity stirring slurry, and water is added to adjust the viscosity of the slurry, and then the binder is added. At a dispersion line speed of 4-10m / s, at 25-35°C, stir for 20-40 minutes, and finally vacuum treat for 20-40 minutes to obtain a sodium ion battery hard carbon negative electrode slurry.
[0019] Preferably, in the above technical solution, the thickener is sodium carboxymethyl cellulose.
[0020] Preferably, in the above technical solution, the active material is hard carbon.
[0021] Preferably, in the above technical solution, the thickener and deionized water in the thickener solution are mixed in a mass ratio of 1:48-150. The mass ratio of the amount of thickener used in the thickener solution to the amount of active substance used is 1:400-500.
[0022] Preferably, in the above technical solution, the binder is PAA.
[0023] Preferably, in the above technical solution, the mass ratio of the amount of binder to the amount of active substance used is 1:35-100.
[0024] Preferably, in the above technical solution, the dispersant includes at least one of polyvinyl pyrrolidone, polyethylene glycol, glyceryl acrylate and cocoyl diethanolamine.
[0025] Preferably, in the above technical solution, the mass ratio of the amount of dispersant used to the amount of active substance used is 1:50-250.
[0026] Preferably, in the above technical solution, the conductive agent is at least one of Super P, Ketjen black, and CNT.
[0027] Preferably, in the above technical solution, the mass ratio of the amount of the conductive agent used to the amount of the active material used is 1:46-100.
[0028] Preferably, in the above technical solution, the mass ratio of the amount of thickener used to the amount of active substance used in the dispersed powder is 1:180-220.
[0029] Preferably, in the above technical solution, the active substance is divided into 2-4 equal portions and added in batches for mixing.
[0030] Preferably, in the above technical solution, the solid content of the dispersed powder is 92-95%.
[0031] Preferably, in the above technical solution, after adding water to adjust the viscosity, the viscosity is 3000-5000 mPa•s.
[0032] Preferably, in the above technical solution, the binder is SBR.
[0033] Preferably, in the above technical solution, the mass ratio of the amount of the binder used to the amount of the active substance used is 1:23-100.
[0034] The invention discloses a method for preparing eleostearic acid glyceryl acrylate:
[0035] Potassium hydroxide, 90% methanol and tung oil are mixed and reacted for 1.5-3 h to obtain a reaction product, and the reaction product is decolorized and filtered to obtain a filtrate, which is treated and dried at 45-55°C for 2.5-5 h to obtain potassium tung oil. Potassium tung oil, anhydrous ethanol and epichlorohydrin are mixed and reacted for 3.5-5 h, and then evaporated to obtain a residual liquid, and the organic layer in the residual liquid is separated and treated, and finally dried to obtain oleic acid glycidyl ester. Tung oil glycidyl ester, tetrabutylammonium bromide, hydroquinone and acrylic acid are mixed, reacted at 105-115°C until the acid value no longer decreases, and a reactant is obtained. Ethyl acetate is added to the reactant to dilute it, and then washed with water, and the ethyl acetate is removed under reduced pressure, and vacuum dried to obtain tung oil acid glyceryl acrylate.
[0036] Preferably, in the preparation of tung oil glyceryl acrylate, the amount of potassium hydroxide in 90% methanol is 0.05-0.09 g / ml, and the mass ratio of the amount of potassium hydroxide used to the amount of tung oil used is 1:4-5.
[0037] Preferably, in the preparation of eleostearic acid glyceryl acrylate, the amount of potassium eleostearate in anhydrous ethanol is 0.2-0.3 g / ml, and the volume ratio of the amount of anhydrous ethanol used to the amount of epichlorohydrin used is 1:0.2-0.4.
[0038] Preferably, in the preparation of eleostearic acid glyceryl acrylate, the mass ratio of eleostearic acid glycidyl acrylate to tetrabutylammonium bromide is 1:0.01-0.02, the mass ratio of eleostearic acid glycidyl acrylate to hydroquinone is 1:0.015-0.025, and the mass ratio of eleostearic acid glycidyl acrylate to acrylic acid is 1:0.18-0.3.
[0039] Preferably, in the present invention, when preparing the hard carbon negative electrode slurry for the sodium ion battery, on the basis of using the dispersants tung oil glyceryl acrylate and cocoyl diethanolamine, artemisia polysaccharide can also be used. The use of artemisia polysaccharide can increase the uniformity and safety of the active material during pulping, play a bonding role between the active material particles, maintain the bonding effect between the active material and the current collector, and improve the conductivity of the electrode sheet and the electrochemical performance of the sodium ion battery.
[0040] Preferably, the mass ratio of Artemisia sphaerocephala polysaccharide to the active substance is 1:40-60, the mass ratio of elaeolate glyceryl acrylate to the active substance is 1:150-750, and the mass ratio of cocoyl diethanolamine to the active substance is 1:150-750.
[0041] Preferably, the present invention also provides a sodium ion battery hard carbon negative electrode slurry prepared by the above preparation method.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The sodium ion battery hard carbon negative electrode slurry of the present invention comprises: an active material, a conductive agent, a thickener, an adhesive, a binder, a dispersant and a solvent; firstly, a thickener solution and a dispersed powder are prepared, and then the thickener solution and the dispersed powder are stirred and dispersed to obtain a high-viscosity stirred slurry, and the slurry viscosity is adjusted to obtain an adjusted slurry, SBR is added to the adjusted slurry and stirred and dispersed to obtain a low-viscosity slurry, and finally a sodium ion battery hard carbon negative electrode slurry is obtained by vacuum treatment. The sodium ion battery hard carbon negative electrode slurry prepared by the present invention has a lower fineness, and the conductivity of the prepared pole piece has a higher conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0045] Figure 1 is the infrared spectrum of eleostearyl acrylate;
[0046] Figure 2 Conductivity diagram of negative electrode sheet prepared from hard carbon negative electrode slurry for sodium ion battery. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.
[0049] Embodiment 1:
[0050] Preparation of hard carbon negative electrode slurry for sodium ion battery: First, sodium carboxymethyl cellulose is added to water and stirred for 200 minutes to obtain a mixed solution, PAA is added to the mixed solution and stirred for 30 minutes, and then polyvinyl pyrrolidone is added to the mixed solution and stirred for 30 minutes to obtain a thickener solution. Then, hard carbon, Super P, sodium carboxymethyl cellulose and water are mixed and stirred for 10 minutes, and then dispersed at a dispersion line speed of 12m / s for 50 minutes to obtain a dispersed powder. Then, the thickener solution and the dispersed powder are stirred and dispersed at a dispersion line speed of 18m / s for 100 minutes to obtain a high-viscosity stirring slurry, and water is added to the high-viscosity stirring paddle to adjust the viscosity to 5000 mPa•s to obtain an adjusted slurry, and then SBR is added to the adjusted slurry, and stirred at a dispersion line speed of 5m / s at 30°C for 30 minutes to obtain a low-viscosity slurry, and the low-viscosity slurry is vacuum treated for 25 minutes to obtain a hard carbon negative electrode slurry for sodium ion batteries. The sodium carboxymethyl cellulose and deionized water in the thickener solution are mixed in a mass ratio of 1:76.92, the mass ratio of the amount of sodium carboxymethyl cellulose in the thickener solution to the amount of hard carbon is 1:447.62, the mass ratio of the amount of PAA to the amount of hard carbon is 1:47, the mass ratio of the amount of polyvinyl pyrrolidone to the amount of hard carbon is 1:235, the mass ratio of the amount of Super P to the amount of hard carbon is 1:94, the mass ratio of the amount of sodium carboxymethyl cellulose in the dispersed powder to the amount of hard carbon is 1:191.84, the hard carbon is divided into three equal parts and added in batches for mixing, the solid content of the dispersed powder is 93%, and the mass ratio of the amount of SBR to the amount of hard carbon is 1:94.
[0051] Embodiment 2:
[0052] Preparation of tung oil acid glyceryl acrylate: Potassium hydroxide, 90% methanol and tung oil are mixed and refluxed for 2 h to obtain a reaction product, activated white clay is added to the reaction product for decolorization, and then the filtrate is filtered to obtain a filtrate, the methanol is evaporated, and the filter cake is washed and then dried at 50°C for 3 h to obtain potassium tung oil. Potassium tung oil acid, anhydrous ethanol and epichlorohydrin are mixed and refluxed for 4 h. After the reaction is completed, ethanol and epichlorohydrin are removed by rotary evaporation to obtain a residual liquid. The organic layer in the residual liquid is separated, washed, and vacuum dried to obtain oleic acid glycidyl ester. Tung oil acid glycidyl ester, tetrabutylammonium bromide, hydroquinone and acrylic acid are mixed, reacted at 110°C until the acid value no longer decreases, and the reaction is stopped to obtain the reactant. Ethyl acetate is added to the reactant to dilute it, then washed with water, ethyl acetate is removed under reduced pressure, and vacuum dried to obtain tung oil acid glyceryl acrylate. The amount of potassium hydroxide in 90% methanol is 0.071 g / ml, the mass ratio of potassium hydroxide to tung oil is 1:4.71, the amount of potassium eleostearate in anhydrous ethanol is 0.25 g / ml, the volume ratio of anhydrous ethanol to epichlorohydrin is 1:0.25, the mass ratio of eleostearic acid glycidyl ester to tetrabutylammonium bromide is 1:0.014, the mass ratio of eleostearic acid glycidyl ester to hydroquinone is 1:0.02, and the mass ratio of eleostearic acid glycidyl ester to acrylic acid is 1:0.229.
[0053] Preparation of hard carbon negative electrode slurry for sodium ion battery: First, sodium carboxymethyl cellulose is added to water and stirred for 200 minutes to obtain a mixed solution, PAA is added to the mixed solution and stirred for 30 minutes, and then polyvinyl pyrrolidone, tung oil acid glyceryl acrylate and coconut oil diethanolamine are added to the mixed solution and stirred for 30 minutes to obtain a thickener solution. Then, hard carbon, SuperP, sodium carboxymethyl cellulose and water are mixed and stirred for 10 minutes, and then dispersed at a dispersion line speed of 12m / s for 50 minutes to obtain a dispersed powder. Then, the thickener solution and the dispersed powder are stirred and dispersed at a dispersion line speed of 18m / s for 100 minutes to obtain a high-viscosity stirring slurry, and water is added to the high-viscosity stirring paddle to adjust the viscosity to 5000 mPa•s to obtain an adjusted slurry, and then SBR is added to the adjusted slurry, and stirred at a dispersion line speed of 5m / s at 30°C for 30 minutes to obtain a low-viscosity slurry, and the low-viscosity slurry is vacuum treated for 25 minutes to obtain a hard carbon negative electrode slurry for sodium ion batteries. The sodium carboxymethyl cellulose and deionized water in the thickener solution are mixed in a mass ratio of 1:76.92, the mass ratio of the amount of sodium carboxymethyl cellulose in the thickener solution to the amount of hard carbon is 1:447.62, the mass ratio of the amount of PAA to the amount of hard carbon is 1:47, the mass ratio of the amount of polyvinyl pyrrolidone to the amount of hard carbon is 1:235, the mass ratio of the amount of tung oil acid glyceryl acrylate to the amount of hard carbon is 1:250, the mass ratio of the amount of cocoyl diethanolamine to the amount of hard carbon is 1:275, the mass ratio of the amount of Super P to the amount of hard carbon is 1:94, the mass ratio of the amount of sodium carboxymethyl cellulose in the dispersed powder to the amount of hard carbon is 1:191.84, the hard carbon is divided into three equal parts and added in batches for mixing, the solid content of the dispersed powder is 93%, and the mass ratio of the amount of SBR to the amount of hard carbon is 1:94.
[0054] Embodiment 3:
[0055] The preparation of eleostearic acid glyceryl acrylate is the same as that in Example 2.
[0056] Preparation of hard carbon negative electrode slurry for sodium ion battery: The preparation of hard carbon negative electrode slurry for sodium ion battery in this embodiment is compared with that in Example 1, except that the mass ratio of tung oil acid glyceryl acrylate to hard carbon in this embodiment is 1:300, and other conditions and parameters are the same as Example 2.
[0057] Embodiment 4:
[0058] The preparation of eleostearic acid glyceryl acrylate is the same as that in Example 2.
[0059] Preparation of hard carbon negative electrode slurry for sodium ion battery: The preparation of hard carbon negative electrode slurry for sodium ion battery in this embodiment is compared with that in Example 1, except that the mass ratio of the amount of coconut oil diethanolamine used to the amount of hard carbon used in this embodiment is 1:305, and other conditions and parameters are the same as Example 2.
[0060] Embodiment 5:
[0061] The preparation of eleostearic acid glyceryl acrylate is the same as that in Example 2.
[0062] Preparation of hard carbon negative electrode slurry for sodium ion battery: First, sodium carboxymethyl cellulose is added to water and stirred for 200 minutes to obtain a mixed solution, PAA and Artemisia polysaccharide are added to the mixed solution and stirred for 30 minutes, and then polyvinyl pyrrolidone, tung oil acid glyceryl acrylate and coconut oil diethanolamine are added to the mixed solution and stirred for 30 minutes to obtain a thickener solution. Then, hard carbon, Super P, sodium carboxymethyl cellulose and water are mixed and stirred for 10 minutes, and then dispersed at a dispersion line speed of 12m / s for 50 minutes to obtain a dispersed powder. Then, the thickener solution and the dispersed powder are stirred and dispersed at a dispersion line speed of 18m / s for 100 minutes to obtain a high-viscosity stirring slurry, and water is added to the high-viscosity stirring paddle to adjust the viscosity to 5000 mPa•s to obtain an adjusted slurry, and then SBR is added to the adjusted slurry, and stirred at a dispersion line speed of 5m / s at 30°C for 30 minutes to obtain a low-viscosity slurry, and the low-viscosity slurry is vacuum treated for 25 minutes to obtain a hard carbon negative electrode slurry for sodium ion batteries. The sodium carboxymethyl cellulose and deionized water in the thickener solution are mixed in a mass ratio of 1:76.92, the mass ratio of the amount of sodium carboxymethyl cellulose in the thickener solution to the amount of hard carbon is 1:447.62, the mass ratio of the amount of PAA to the amount of hard carbon is 1:47, the mass ratio of the amount of Artemisia sphaerocephala polysaccharide to the amount of hard carbon is 1:50, the mass ratio of the amount of polyvinyl pyrrolidone to the amount of hard carbon is 1:235, the mass ratio of the amount of tung oil acid glyceryl acrylate to the amount of hard carbon is 1:250, the mass ratio of the amount of cocoyl diethanolamine to the amount of hard carbon is 1:275, the mass ratio of the amount of Super P to the amount of hard carbon is 1:94, the mass ratio of the amount of sodium carboxymethyl cellulose in the dispersed powder to the amount of hard carbon is 1:191.84, the hard carbon is divided into three equal parts and added in batches for mixing, the solid content of the dispersed powder is 93%, and the mass ratio of the amount of SBR to the amount of hard carbon is 1:94.
[0063] Experimental Example 6:
[0064] The preparation of eleostearic acid glyceryl acrylate is the same as that in Example 2.
[0065] Preparation of hard carbon negative electrode slurry for sodium ion battery: The preparation of hard carbon negative electrode slurry for sodium ion battery in this embodiment is compared with that in Example 5, except that the mass ratio of the amount of Artemisia sphaerocephala polysaccharide used to the amount of hard carbon used in this embodiment is 1:60, and other conditions and parameters are the same as in Example 2.
[0066] Comparative Example 1:
[0067] Preparation of hard carbon negative electrode slurry for sodium ion battery: The preparation of hard carbon negative electrode slurry for sodium ion battery in this embodiment is compared with that in Example 2, except that eleostearic acid glyceryl acrylate is not added in this embodiment, and other conditions and parameters are the same as in Example 2.
[0068] Comparative Example 2:
[0069] The preparation of eleostearic acid glyceryl acrylate is the same as that in Example 2.
[0070] Preparation of hard carbon negative electrode slurry for sodium ion battery: The preparation of hard carbon negative electrode slurry for sodium ion battery in this embodiment is compared with that in Example 2, except that coconut oil diethanolamine is not added in this embodiment, and other conditions and parameters are the same as in Example 2.
[0071] Experimental Example 1:
[0072] The glyceryl acrylate prepared in Example 2 was characterized by infrared spectroscopy analysis in the scanning range of 400-4000 cm -1 The results are as follows Figure 1 As shown, 3000-3100cm -1 It is the unsaturated =CH absorption peak, 2853cm -1 and 2872cm -1 -CH absorption peaks of -CH3 and -CH2; 1700-1800cm -1 is the absorption peak of C=O, and 1200-1300cm -1 and 1000-1100cm -1 Absorption peak of (O=)COC; 700-800cm -1 There is a strong and broad -CH2- absorption peak, which is consistent with the structural characteristics of tung oil acid glyceryl acrylate.
[0073] Experimental Example 2:
[0074] The sodium ion battery hard carbon negative electrode slurry prepared in Examples 1-6 and Comparative Examples 1-2 was uniformly coated on an aluminum foil, dried at 80° C., rolled under a pressure of 1.5 MPa, cut into pieces of the desired size to obtain negative electrode sheets, and the conductivity was measured.
[0075] The results are as follows Figure 2As shown, the conductivity of the electrode sheet made of the hard carbon negative electrode slurry for sodium ion batteries prepared in Example 2 is higher than that in Example 1, indicating that the use of tung oil glyceryl acrylate and cocoyl diethanolamine is beneficial to improving the dispersion performance of the electrode slurry, reducing the presence of particulate matter, and thus improving the conductivity; Example 5 Compared with Example 2, the conductivity of the electrode sheet made of the hard carbon negative electrode slurry for sodium ion batteries prepared in Example 5 is higher, indicating that by adding artemisia polysaccharide on the basis of using tung oil glyceryl acrylate and cocoyl diethanolamine, the hard carbon material and the conductive agent can be better adhered to the current collector, and they are in close contact with each other to reduce the electrode sheet resistance, maintain good mechanical properties, tolerance and electrode sheet integrity, thereby improving conductivity. Compared with Comparative Examples 1 and 2, the conductivity of the electrode sheet made of the hard carbon negative electrode slurry for sodium ion batteries prepared in Example 2 is lower than that of Comparative Examples 1 and 2, indicating that tung oil acid glyceryl acrylate and cocoyl diethanolamine need to be used at the same time and work together. The use of tung oil acid glyceryl acrylate and cocoyl diethanolamine alone has no obvious effect on the conductivity of the electrode sheet made of the hard carbon negative electrode slurry for sodium ion batteries.
[0076] Experimental Example 3:
[0077] The first coulombic efficiency was determined by making the hard carbon negative electrode slurry for sodium ion batteries prepared in Examples 1-6 and Comparative Examples 1-2 into negative electrode sheets, winding the negative electrode sheets and the positive electrode sheets to obtain a winding core, which was placed in an aluminum shell and injected with electrolyte to seal the sodium ion battery, and the first coulombic efficiency of the sodium ion battery was determined.
[0078] Table 1 Results of the first coulombic efficiency measurement
[0079]
[0080] The results are shown in Table 1. The first coulombic efficiency of the sodium ion battery made from the hard carbon negative electrode slurry for sodium ion battery prepared in Example 2 is higher than that in Example 1, indicating that the use of tung oil acid glyceryl acrylate and cocoyl diethanolamine can effectively reduce the interfacial impedance and improve the first coulombic efficiency; the first coulombic efficiency of the sodium ion battery made from the hard carbon negative electrode slurry for sodium ion battery prepared in Example 5 is higher than that in Example 2, indicating that the use of artemisia polysaccharide on the basis of using tung oil acid glyceryl acrylate and cocoyl diethanolamine can further optimize the performance of the sodium ion battery and improve the first coulombic efficiency; compared with Comparative Examples 1 and 2, the first coulombic efficiency of the sodium ion battery made from the hard carbon negative electrode slurry for sodium ion battery prepared in Example 2 is lower than that of Comparative Examples 1 and 2, indicating that tung oil acid glyceryl acrylate and cocoyl diethanolamine need to be used at the same time and work together, and the use of tung oil acid glyceryl acrylate and cocoyl diethanolamine alone has no obvious effect on improving the first coulombic efficiency of the sodium ion battery.
[0081] Experimental Example 4:
[0082] The hard carbon negative electrode slurry for sodium ion batteries prepared in Examples 1-6 and Comparative Examples 1-2 was made into a negative electrode sheet, the negative electrode sheet and the positive electrode sheet were wound to obtain a core, the core was placed in an aluminum shell and injected with electrolyte to seal, to obtain a sodium ion battery, and the capacity retention rate of the sodium ion battery after 1000 cycles was measured.
[0083] Table 2 Cycle capacity retention rate measurement results
[0084]
[0085] The results are shown in Table 2. The capacity retention rate of the sodium ion battery made from the hard carbon negative electrode slurry for sodium ion battery prepared in Example 2 is higher than that in Example 1, indicating that the use of tung oil acid glyceryl acrylate and cocoyl diethanolamine can effectively improve the capacity retention rate, that is, the cycle life; the capacity retention rate of the sodium ion battery made from the hard carbon negative electrode slurry for sodium ion battery prepared in Example 5 is higher than that in Example 2, indicating that the use of artemisia polysaccharide on the basis of using tung oil acid glyceryl acrylate and cocoyl diethanolamine can further improve the capacity retention rate; compared with Comparative Examples 1 and 2, the capacity retention rate of the sodium ion battery made from the hard carbon negative electrode slurry for sodium ion battery prepared in Example 2 is lower than that of Comparative Examples 1 and 2, indicating that tung oil acid glyceryl acrylate and cocoyl diethanolamine need to be used together, and the use of tung oil acid glyceryl acrylate and cocoyl diethanolamine alone has no obvious effect on improving the capacity retention rate of the sodium ion battery.
[0086] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.
[0087] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.
Claims
1. A method for preparing a hard carbon negative electrode slurry for a sodium ion battery, comprising: The thickener is first mixed with water and stirred, and then a binder and a dispersant are added in sequence and stirred to obtain a thickener solution; the active material, the conductive agent, the thickener and the water are stirred and mixed, and then dispersed to obtain a dispersed powder; then the obtained thickener solution and the dispersed powder are stirred and dispersed to obtain a high-viscosity stirred slurry, and the slurry viscosity is adjusted, and then a binder is added and stirred and dispersed, and vacuum treatment is performed to obtain a sodium ion battery hard carbon negative electrode slurry; The thickener is sodium carboxymethyl cellulose; the thickener and deionized water in the thickener solution are mixed in a mass ratio of 1:48-150, and the mass ratio of the amount of the thickener in the thickener solution to the amount of the active substance is 1:400-500; the binder is PAA, and the mass ratio of the amount of the binder to the amount of the active substance is 1:35-100; the dispersants are tung oil acid glyceryl acrylate and cocoyl diethanolamine, the mass ratio of the amount of tung oil acid glyceryl acrylate to the amount of the active substance is 1:150-750, and the mass ratio of the amount of cocoyl diethanolamine to the amount of the active substance is 1:150-750.
2. The method for preparing a hard carbon negative electrode slurry for a sodium ion battery according to claim 1, characterized in that: The active material is hard carbon, the conductive agent is at least one of Super P, Ketjen black, and CNT, the mass ratio of the conductive agent to the active material is 1:46-100, the mass ratio of the thickener in the dispersed powder to the active material is 1:180-220, and the solid content of the dispersed powder is 92-95%.
3. The method for preparing a hard carbon negative electrode slurry for a sodium ion battery according to claim 1, characterized in that: The viscosity of the adjusted slurry is 3000-5000 mPa•s; the binder is SBR, and the mass ratio of the amount of SBR used to the amount of active substance used is 1:23-100.
4. The method for preparing a hard carbon negative electrode slurry for a sodium ion battery according to claim 1, characterized in that: During the preparation of the thickener solution, the thickener and water are mixed and stirred for 180-240 minutes, the stirring time after adding the binder is 25-40 minutes, and the stirring time after adding the dispersant is 25-40 minutes; during the preparation of the dispersed powder, the stirring and mixing time is 8-15 minutes, the dispersion line speed is 10-15 m / s, and the dispersion time is 40-60 minutes.
5. The method for preparing a hard carbon negative electrode slurry for a sodium ion battery according to claim 1, characterized in that: The thickener solution and the dispersed powder are stirred and dispersed at a dispersion line speed of 17-20 m / s, and the stirring and dispersing time is 90-120 min. After SBR is added, the stirring and dispersing dispersion line speed is 4-10 m / s, the stirring and dispersing temperature is 25-35° C., and the stirring and dispersing time is 20-40 min.
6. A sodium ion battery hard carbon negative electrode slurry prepared by the method according to any one of claims 1 to 5.
7. A battery, comprising a negative electrode sheet obtained by coating the sodium ion battery hard carbon negative electrode slurry according to claim 6 on an aluminum foil.
8. A vehicle comprising the battery according to claim 7.
Citation Information
Patent Citations
Negative pole slurry of lithium ion battery, rapid preparation method thereof and negative pole piece of lithium ion battery
CN107293706A
Lithium battery negative electrode slurry and homogenizing process thereof
CN115763788A